2012
DOI: 10.1177/1049732312448541
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Public Involvement in the Coproduction of Knowledge

Abstract: Patient and public involvement in health research is increasingly well established internationally, but the impacts of involvement on the research process are hard to evaluate. We describe a process of qualitative data analysis in a mental health research project with a high level of mental health service user and carer involvement, and reflect critically on how we produced our findings. Team members not from research backgrounds sometimes challenged academic conventions, leading to complex findings that would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 31 publications
2
116
0
1
Order By: Relevance
“…These add to those achievements and benefits of wider SUAC participation reported elsewhere (e.g. Barber et al, 2011;Brett et al, 2014;Faulkner, 2010;Gillard & Stacey, 2005;Gillard et al 2012;Hutchinson & Lovell, 2013;Patterson et al, 2014;Wallcraft et al, 2012). Other findings of this study, such as those that perceive considerable benefits to the education of students, corroborate other non-SUAC led research findings about such benefits (e.g.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These add to those achievements and benefits of wider SUAC participation reported elsewhere (e.g. Barber et al, 2011;Brett et al, 2014;Faulkner, 2010;Gillard & Stacey, 2005;Gillard et al 2012;Hutchinson & Lovell, 2013;Patterson et al, 2014;Wallcraft et al, 2012). Other findings of this study, such as those that perceive considerable benefits to the education of students, corroborate other non-SUAC led research findings about such benefits (e.g.…”
Section: Discussionsupporting
confidence: 64%
“…Barber et al, 2011;Brett et al, 2014;Faulkner, 2010;Gillard & Stacey, 2005;Gillard, et al 2012;Hutchinson & Lovell, 2013;Patterson et al, 2014;Wallcraft et al, 2012), which particularly relates to the healthoriented Patient and Public Involvement (PPI) literature. With regard to the effect of SUAC involvement in research, Brett et al (2014) systematically reviewed 66 studies of PPI involvement and demonstrated that, despite a relatively weak evidence base (due partly to the nature of SUAC involvement not always being made clear), health and social work research has benefitted from PPI in the enhancement of the quality of research and in having better assured its appropriateness and relevance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…27,28 This study was largely undertaken -in terms of fieldwork, data collection and analysis -by two researchers with personal lived experience of mental health problems (hereafter referred to as service user researchers).…”
Section: Service User Researchers and 'Coproduction' In The Research mentioning
confidence: 99%
“…-is taken into account. 28 Employing peer workers in mental health services can be described in terms of the coproduction of mental health care. This study is underpinned by a coproduction approach to the research process.…”
Section: Service User Researchers and 'Coproduction' In The Research mentioning
confidence: 99%
“…We believe this can be beneficial to both research and practice partners, and is a useful adjunct to the peer reviewed paper as legitimate academic output which has been defined as problematic for some stakeholders in co-production partnerships. 19 …”
Section: Actionable Outputs and Tangible Returnsmentioning
confidence: 99%